TOTAL QUALITY MANAJEMEN (TQM) SEBAGAI MANAJEMEN MUTU ALTERNATIF PADA PROGRAM STUDI PENDIDIKAN BAHASA ARAB - Nur Fuadah; Eka Silfia Khumairah; Muhammad Jidan Badarab; Lailatul Rifqoh Izzati (university Of islam, 2023)
The Arabic Language Education Study Program at the University of Muhammadiyah Malang is currently one of the PTMs that is trying to develop the quality of its education so that it can produce quality graduates. The results of this observation are 1) TQM management as an integrated alternative quality management in the Arabic language education study program at the University of Muhammadiyah Malang is carried out using performance indicators for organizers of study program academic activities consisting of input indicators, process indicators and output indicators. In implementing TQM for the UMM Arabic language education study program, there are four main elements that are continuously considered, namely customers, respect for everyone, management based on facts, and continuous improvement. The cycles carried out in the UMM Malang Arabic language education study program to maintain its quality include planning, implementation and evaluation. 2) Supporting factors for managing quality management in the Arabic Language Education Program at the University of Muhammadiyah Malang, namely leadership, students, lecturers, curriculum and collaboration networks. The inhibiting factors are no support from the external environment, inappropriate curriculum, lack of commitment from all stakeholders in the UMM Malang PBA study program, lack of management.